Theatre, Gender Diversity and Border Pedagogy - Vargas, Vagner de Souza; Bussoletti, Denise Marcos (Diálogos Latinoamericanos, 2015)
The way as society deals, understands and treats gender diversity affects drastically the relationships for people who are identified as transgender, transsexual, as well as those identified as gender fluid or non-binary gender. Our group from a university in southern Brazil develops several activities seeking dialogue with different social groups, bringing diversity as an issue for debates, actions and thoughts. Through interventions, artistic presentations and educational activities, we promote debates and reflection, and encourage the understanding of and respect for diversity in society. The aim of this article is to describe a project about theatre playwriting addressing diversity as the central theme. Furthermore, we explain how these actions are guided in our proposals for a Border Pedagogy and Aesthetics of Ginga. Dealing with these issues in our local society, the playwritings were fundamental for unveiling these people and stimulating their self-esteem by showing their stories as nobody else had done before.